Еlectronic fire safety systems efficiency in the combustion zone of cars for underground parkings of residential buildings - V. V. Khoroshko; R. V. Hlinisty; R. R. Hlinisty; E. N. Shneiderov; A. G. Korolev; O. M. Korol (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
In this paper we presents the results of tests of automatic fire alarm systems in terms of reducing the temperature effect on building structures (floors), air ducts of the exhaust smoke ventilation system. Tests were carried out to determine the efficiency of the antismoke ventilation system for the removal of combustion products through steel air ducts with a metal thickness of 1 mm, as well as analysis of the temperature regime on building structures, the air duct of the exhaust smoke ventilation system under fire exposure. For the warning system (SO) of the second type, CO-2 we used on the basis of ISO “Bolid” devices. The launch of a fire warning system is provided for: automatically from an automatic fire extinguishing system; remotely from manual fire detectors installed at emergency exits from the vehicle storage room. Two full-scale firing tests were carried out for passenger cars. During the tests, the vehicles were ignited from inside the passenger compartment. In the course of the fire tests proved that the antismoke control ventilation ducts retained their integrity and tightness, which was confirmed by the positive protocols of aerodynamic tests of the smoke control ventilation system. The air ducts of the exhaust smoke ventilation system retained their integrity, the flange connections of the air ducts retained their strength and tightness, the fastenings of the air ducts were not damaged and retained their functions. The tests established the following: limitation of the fire center in the horizontal projection of the vehicle (the perimeter of the vehicle); filling the volume of the storage room for vehicles with a smoke-steam-air mixture occurs in an avalanche manner over the entire height of the room; as a result of the avalanche-like filling of the room, the absence of a neutral zone (security zone) was determined. Based on the results of the tests, it is possible to make changes to the existing technical normative legal acts.